Acute effect of lower limbs self-massage and passive stretching on vertical jump performance (Research, Society and Development, 2021)
The purpose of the present study was to verify the acute effect of static stretching and foam rolling self-massage on the lower limbs on vertical jump performance. Ten physically active and apparently healthy women participated in the present study. Participants performed two protocols with random entry, conducted using the Latin square technique: 1) control condition (CC), 2) self-massage via foam rolling (FR), and 3) static stretching (SS). The Sargent Jump Test was used to assess the lower limbs muscle power being performed before the FR and SS conditions. Both FR and SS conditions were performed for the anterior and posterior thigh and posterior leg regions in 4 sets with 30 seconds duration for each position, respecting a passive recovery of 30 seconds between each set. Both SS (p = 0.010) and FR condition (p = 0.042) significantly increased the distance reached in jumps in comparison to CC. No statistical difference was observed between experimental conditions (FR vs SS) (p = 1.000). According to the present study results both pre-exercise strategies (FR and SS) seem to improve the lower limbs muscle power in the Sargent Jump Test.